Functional significance of mixed-species groups for zebra (Equus quagga) in savanna habitats - Corry-Roberts, Carys Alexandra (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Globally, herbivore populations are facing decline, which threatens their crucial role within the ecosystems they inhabit. Herbivores are essential to ecosystem structure and function because they act as prey for higher trophic levels, cycle soil nutrients, and alter vegetation structure. Understanding the drivers that shape herbivore habitat use and selection are therefore critical for making informed conservation and management decisions. Like all prey species, herbivores must balance a trade-off between acquiring resources and avoiding predation which is influenced by a number of species-specific intrinsic traits and various ecological drivers. Herbivores can also track risk over space and time, and certain habitat structures and landscape features can influence risk perception; this is termed the landscape of fear. To mitigate the risk-reward trade-off, herbivores employ a suite of behavioural responses. Group formation is likely the most well-documented of these responses. However, grouping results in the information-competition trade-off, wherein group members may obtain valuable information regarding the location of resources and/or the risk of predation, but may suffer from increased competition, especially among larger group sizes. Mixed-species groups"”an assemblage of two or more species in close spatial association"”have the potential to mitigate some of the competitive costs of larger conspecific groups and enhance the anti-predator and/or foraging benefits of grouping. African savannas provide a particularly useful natural laboratory to study mixed-species groups, due to the high diversity of prey species and habitat heterogeneity present. Previous studies have investigated the mixed-species effect within these systems, but have yet to quantify some of the identity-dependent costs and benefits associated with mixed-species herding. Thus, the overall aim of my study was to quantify the functional significance of mixed-species groups for zebra (Equus quagga) herding with two of their most common herding partners, impala (Aepyceros melampus) and wildebeest (Connochaetes taurinus). My study was conducted at multiple spatial scales in the southern portion of the Kruger National Park, South Africa between 2021 and 2022. I found that mixed-species herding altered zebra landscape use, resulting in a quantifiable intensification of habitat use compared to when they herd with conspecifics. I did not observe significant habitat expansion for zebra in mixed-species herds compared to single-species herds, likely because the anti-predator benefits of mixed-species herding convey enhanced foraging opportunities in already-safe habitats. Zebra foraging with impala achieved greater foraging success and experienced lower levels of competition, compared to zebra foraging with wildebeest. However, compared to foraging with conspecifics, the levelled landscape of fear zebra experienced when foraging with wildebeest resulted in increased foraging success across the landscape. My findings highlight the context-dependency of the costs and benefits associated with different herding partners for zebra, and suggest that in mixed-species herds with wildebeest, zebra experience increased potential fitness benefits compared to herding with impala or conspecifics. Overall, the findings of my study suggest that mixed-species herding is an important tool in the suite of anti-predator behaviours employed by prey species, and one with significant implications for survivorship, habitat use, and ultimately, community level interactions.
Keywords: Herding behavior in animals; Zebras -- Food; Foraging; Zebras -- Behavior; Zebras -- Conservation; Herbivores -- Habitat